Madrasah Ibtidaiyah as Guardians of Tradition: A Socio-Anthropological Study of Local Religious Heritage - Ana Quthratun Nada; Sri Sumarni; Farida Hanum (Mentari : Journal of Islamic Primary School, 2025)
This study aims to examine the role of Madrasah Ibtidaiyah in preserving local religious traditions in Indonesia through a socio-anthropological approach. As an Islamic primary education institution, Madrasah Ibtidaiyah not only provides academic instruction but also functions as a guardian of students’ religious and social identities. Amid the strong currents of globalization, these madrasahs face challenges in maintaining local religious traditions such as the celebration of the Prophet’s Birthday (Maulid Nabi), tahlilan, and collective dhikr, which are increasingly being displaced by modern culture. This study employs a literature review method to explore various strategies implemented by madrasahs in integrating traditional values into the curriculum and extracurricular activities. The findings indicate that tradition-based education in Madrasah Ibtidaiyah contributes significantly to the formation of students’ religious identities and the strengthening of social cohesion within the community. This study highlights the importance of innovation in relevant learning methods to ensure the sustainability of local religious traditions in the era of modernization.